Climate variations in a high altitude Alpine basin and their effects on a glacial environment (Italian Western Alps) - Giaccone E.; Paro L.; COLOMBO, NICOLA; ACQUAOTTA, FIORELLA; FRATIANNI, SIMONA (Atmósfera, 2015)
The main objective of this study is to evaluate the variations of climatic parameters (temperature, rain and snow) measured by two weather stations (Formazza and Sabbione) that have never been analyzed before, located in a high glacial catchment (the Sabbione basin in the Italian Western Alps). The study highlights the climatic evolution of the alpine basin during the last 60 years (1950-2012): climate change has caused a pronounced glacial decline originated by ablation augmentation, due mainly to increasing air temperatures and to reduced alimentation caused by a fresh snow decrease. The cross-correlation test shows that temperatures affect the glacial retreat dynamics more than snowfall. Periglacial and permafrost landforms (e.g., patterned grounds, rock glaciers) have been identified within the Little Ice Age (LIA) glacial deposits, which indicate the ongoing transition from glacial/proglacial to periglacial environments. Furthermore, in order to better identify the periglacial domain in the basin, a map of mean annual air temperature (MAAT) was produced based on climatic analysis.